Interactions among the three adenovirus core proteins. - Chatterjee, P K (1985)
Interactions among the three adenovirus core polypeptides V, VII, and mu were examined, using the reversible chemical cross-linker dithiobis(succinimidyl propionate) and two-dimensional polyacrylamide gel electrophoresis. Cross-linked species obtained from gradient-purified adenovirus type 2 cores were well represented among the cross-linked products of pentonless virions and crude core preparations. The more efficiently formed cross-linked core species were also identified with the arginine-specific cross-linker, p-azidophenyl glyoxal. In addition to dimers of polypeptides V and VII, efficient cross-linking of V to VII, V to mu, and VII to V to mu was detected in adenovirus cores. Notably absent were cross-linked species corresponding to higher multimers of polypeptide VII. A major core-capsid interaction appeared to be via the association of polypeptide V with a dimer of polypeptide VI.